Functional leaf traits indicate phylogenetic signals in forests across an elevational gradient in the central Himalaya - Krishna, Mayank; Winternitz, Jamie; Garkoti, Satish Chandra; Penuelas, Josep (Journal of plant research, 2021)
Traits are the primary attributes that distinguish a species niche. Species and higher taxa are part of a structured phylogeny, and variation in plant traits depends on lineage as well as on environmental conditions. Therefore, it is crucial to investigate linkages between taxonomic identity, shared ancestry, and environment for understanding the variation in leaf traits. We investigated the evolutionary relationships, based on multiple gene sequences among 26 plant species sampled along an elevational gradient from 650 to 3600 m a.s.l. in the central Himalaya. We tested for the phylogenetic signal based on three different measures in 10 leaf traits having a significant association with the resource acquisition-conservation trade-offs axis and influencing plant growth, development, and ecological performance. We further assessed the role of elevation and growth forms as the potential drivers of leaf traits variation while controlling for phylogeny. 5 out of 10 leaf traits showed significant phylogenetic signal. Plant species clustered more often by growth forms at the tips of the phylogeny indicating multiple instances of independent evolution. Evergreen taxa showed niche separation with deciduous and incorporated larger trait variation. Trait variations were guided by both growth forms and elevation when accounted for phylogeny. Growth form has a higher contribution to trait variation compared to elevation. Trade-offs were detected between resource conservation and resource acquisition machinery traits (that would maximise carbon gain), differing between growth forms and along elevation.